Digital Transformation in Financial Management: Its Impact on Investment Decision Making - Misrah; Majid, Abdul (Jurnal Manajemen Dan Bisnis, 2026)
The development of information technology has encouraged companies to carry out digital transformation, especially in the field of financial management, in order to improve the quality of financial information and support more effective and efficient investment decision-making. This study aims to analyze how the implementation of digital transformation in financial management is carried out, how it affects the quality of financial information, and to what extent it contributes to the effectiveness and efficiency of investment decision-making in companies. The research method used is a qualitative descriptive approach with data collection techniques through in-depth interviews, observations, and documentation studies in several companies that have implemented a digital financial management system. The results of the study show that digital transformation is implemented through digitalization of financial processes, transaction automation, cross-functional data integration, and the use of big data technology and artificial intelligence (AI). The application of this technology has been proven to increase the accuracy, relevance, and speed of financial information so as to support management in conducting a more comprehensive investment feasibility analysis. In addition, digital transformation also contributes to accelerating the decision-making process, reducing operational costs, and increasing the company's responsiveness to market changes. This study recommends that companies continue to invest in technology and human resource competency development to optimize the benefits of digital transformation in supporting higher quality investment decisions.